The PhD ‘Dragon’ - Magne Espeland (Cubic Journal, 2024)
In this article I reflect on the meaning, role and significance of educational designs in PhD studies, with the aim of raising some about ‘taming’ the dragon, as well as inviting readers to reflect on their own experiences of such studies as students and/or supervisors.